Martial arts in action - Levigne, Heather, 1974-; Rouse, Bonna (New York : Crabtree, 2001)
Presents an illustrated introduction to various martial arts styles, including karate, tae kwon do, kung fu, jujitsu, judo, aikido, and others.
Includes index.
Resource Links.
4.4
3-6
Keywords: Martial arts for children; Martial arts for children -- Training; Martial arts; Martial arts -- Training; Martial arts; Martial arts -- Training; Martial arts; Self-defense.